Egyptian women workers and entrepreneurs : maximizing opportunities in the economic sphere - Nasr, Sahar (Directions in development (Washington, D.C.). Private sector., 2010)
Over the past decade, Egyptian women have made significant progress in improving their economic and social status. The Egyptian government's commitment to women's empowerment is strong at the highest political level. Yet continued disparities remain in the country's labor market and the business arena. This book analyzes these disparities and makes recommendations for needed change to ensure a level playing field.